Curcumin Produces Protective Effects against Testicular Toxicity Induced By Cadmium in Albino Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The purpose of our study was to evaluate the preventive effects of supplementation with curcumin (Cur) on Cadmium (Cd) induced testicular damage. Young male Wistar albino rats were divided into five groups; Control, Cd, Cur, Cd+Cur, pre-Cur+Cd. Rats were administered an acute dose of CdCl2 at a concentration of 50 mg/kg bw and Cur at 150 mg/kg bw for 15 days. The activities of the stress indicating enzymes (SOD, CAT) and MDA content as a result of LPO along with the total tissue protein and cholesterol were assessed in the testicular homogenate of rats. A significant reduction in the activities of SOD and CAT with parallel significant upsurge in MDA accompanied by a significant reduction in total tissue protein content and a significant rise in tissue cholesterol was observed in rat testes. Also, the reduction in the testicular weights along with a decline in testosterone concentration was detected. Further, Cur supplementation with Cd significantly upturned the Cd-induced variations in oxidative stress indicating enzymes and amended the testosterone levels, total testicular protein, and cholesterol content. Therefore, it can be concluded that Cur plays a protective role against testicular toxicity produced by a single dose of CdCl2.